Digital Transformation of Health: Towards the European Health Data Space - Proso, Maja (Medicine, Law & Society, 2024)
The European space for health data (EHDS) is the first European proposal for the arrangement of a specific area common to the entire EU. The main goals are enabling citizens to control and use their own health data, nationally and throughout the EU (primary use of health data), cross-border exchange of health data and building a single market for digital health services. A further goal is to create an effective legal framework for the use of health data for research and innovation purposes (secondary use of health data), as well as the establishment of electronic health records and the development of a health data management system. In the paper author presents the concept of health data privacy in digital age and analyses the current health data protection legal framework. The paper examines the provisions of the EHDS Proposal, critically analyising the proposed terms of primary and secondary use of health data, as well as it’s rules on data portability and interoperability.